ARCHAEOLOGICAL MONUMENTS OF USTURT OF THE EARLY MIDDLE AGES (V-XI CENTURY) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
There are sources from the early Middle Ages about the region of Usturt bordering the Khorezm oasis. Among them, Ibn Ruste, Al Istahri (IX-X), Ibn Fadlan (922), Al Muqaddasi (985), Ibn Battuta (1333), A. Jenkinson (1558) and scholars of the new era we learned in his works.